Examining sequential mediators in teacher emotional intelligence behaviors and academic engagement. - Extremera-Pacheco, Natalio; Chamizo-Nieto, María Teresa; Rey-Peña, Lourdes (My University, 2024)
Introduction Emotional intelligence of teachers plays a key role in explaining school and affective well-being indicators of their students which is typically related to relevant academic outcomes. However, little is known about the potential underlying mechanisms involved in this linkage. The aim of this paper is to examine the associations between perceived teacher emotional intelligence behaviors and academic engagement through two serial mediators, perceived social support from teachers and positive affect. Method: 442 high school students from two high school centers from Andalusia (Spain) (58.6% girls), ranged from 12-18 years, participated voluntarily in this study. Students completed a scale of teacher emotional intelligence behaviors and perceived social support from teachers at time 1. Five months later (Time 2), measures of positive affect and academic engagement were obtained. Results: After controlling for demographic covariates, the results revealed that: (a) teacher emotional intelligence behaviors (time 1) was positively associated with academic engagement five months later (time 2); (b) both perceived social support from teachers (time 1) and positive affect (time 2) partially mediated the link between teacher emotional intelligence behaviors and academic engagement in a parallel fashion; and (c) social support from teachers and positive affect also sequentially mediated the link between teacher emotional intelligence behaviors and academic engagement. Conclusions: This study provides evidence for the central role of teacher social support and positive affect as mechanisms underlying the linkage between teacher emotional intelligence behaviors and subsequent academic engagement. The findings are discussed in terms of explicating some of the processes through which teacher emotional intelligence behaviors might fostering positive attitudes at school and the way teachers can harness personal resources for students’ engagement and learning.
Keywords: Inteligencia emocional; Profesores - Aspectos psicológicos; Rendimiento académico; Inteligencia emocional del profesorado; Compromiso académico; Apoyo social del profesorado